Prepulse inhibition in euthymic bipolar disorder patients in comparison with control subjects - Santos, J.L.; Mateo, J.; Aparicio, A.; Sánchez-Morla, E.M. (European psychiatry, 2016)
Deficient prepulse inhibition (PPI) of the startle response, indicating sensorimotor gating deficits, has been reported in schizophrenia and other neuropsychiatric disorders. The present study aimed to assess sensorimotor gating deficits in euthymic bipolar patients. Furthermore, we analysed the relationships between PPI and clinical and cognitive measures. PPI was measured in 64 euthymic bipolar patients and in 64 control subjects matched for age, gender, education level and smoking status. Clinical characteristics and level of functioning were assessed in all participants using the Hamilton Depression Rating Scale (HDRS), Young Mania Rating Scale (YMRS) and Functioning Assessment Short Test (FAST). Cognition was evaluated using the MATRICS Consensus Cognitive Battery (MCCB) and the Stroop Test as an additional measure of executive function. Compared with controls, patients with bipolar disorder exhibited PPI deficits at 60- and 120-milliseconds prepulse-pulse intervals. Among patients with bipolar disorder, PPI was correlated with the social cognition domain of the MCCB. PPI was not significantly correlated with other clinical or neurocognitive variables in either group. Our data suggest that PPI deficit is a neurobiological marker in euthymic bipolar disorder, which is associated with social cognition but not with other clinical, functional or cognitive measures.